THE STUDY OF THE MAIN DIRECTIONS OF PERSONALITY EDUCATION AS A SOCIO-PSYCHOLOGICAL PROBLEM (Web of Teachers: Inderscience Research, 2026)
The problem of personality development and the exploration of its key directions have always been among the central issues in psychological and pedagogical sciences. Personality does not develop in isolation, but rather under the influence of social, cultural, and psychological factors. Understanding the main directions of personality education as a socio-psychological problem is important in the study of the harmonious maturation of the individual, the establishment of values, and the formation of socially significant qualities in people.